Reflections on the relevance of updated, standardised, and reliable data on sexual and gender-based violence for research and policymaking for eradication, response, and prevention in Sierra Leone - Zinnya del Villar; Anna Spinardi; Ivette Yáñez; Alina Sotolongo; Ana Deborah Lana; Berenice Fernandez Nieto; Yara Antoniassi; Ricardo Fuentes-Nieva; Emmanuel Letouzé (Data & Policy)
Sexual and gender–based violence (SGBV) is a multifaceted, endemic, and nefarious phenomenon that remains poorly measured and understood, despite greater global awareness of the issue. While efforts to improve data collection methods have increased–including the implementation of the Demographic and Health Survey (DHS) in some countries–the lack of reliable SGBV data remains a significant challenge to developing targeted policy interventions and advocacy initiatives. Using a recent mixed–methods research project conducted by the authors in Sierra Leone as a case study, this paper discusses the current status of SGBV data, challenges faced, and potential research a pproaches.